Evaluation of Reference Genes for Gene Expression Analysis Using Quantitative RT-PCR in Azospirillum brasilense - McMillan, Mary; Pereg, Lily (PLOS ONE, 2014)
Azospirillum brasilense is a nitrogen fixing bacterium that has been shown to have various beneficial effects on plant growth and yield. Under normal conditions A. brasilense exists in a motile flagellated form, which, under starvation or stress conditions, can undergo differentiation into an encapsulated, cyst-like form. Quantitative RT-PCR can be used to analyse changes in gene expression during this differentiation process. The accuracy of quantification of mRNA levels by qRT-PCR relies on the normalisation of data against stably expressed reference genes. No suitable set of reference genes has yet been described for A. brasilense. Here we evaluated the expression of ten candidate reference genes (16S rRNA, gapB, glyA, gyrA, proC, pykA, recA, recF, rpoD, and tpiA) in wild-type and mutant A. brasilense strains under different culture conditions, including conditions that induce differentiation. Analysis with the software programs BestKeeper, NormFinder and GeNorm indicated that gyrA, glyA and recA are the most stably expressed reference genes in A. brasilense. The results also suggested that the use of two reference genes (gyrA and glyA) is sufficient for effective normalisation of qRT-PCR data.